2008
DOI: 10.1007/s11270-008-9620-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Synchronous Fluorescence Technique as a Water Quality Monitoring Tool for an Urban River

Abstract: The development of a monitoring tool for predicting water quality and tracing pollution sources are important for the management of sustainable aquatic ecosystems in urban areas. In this study, synchronous fluorescence technique was applied to 18 sampling sites of a typical urban watershed in Korea, some of which are directly affected by the effluent from a wastewater treatment plant (WWTP), to investigate the capability of the technique for biochemical oxygen demand (BOD) prediction and source discrimination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 26 publications
0
46
0
1
Order By: Relevance
“…However, fluorescence patterns of treated sewage appear to depend on the effluent composition and the type of the treatment operations (Janhom et al 2009). The presence of relatively high PLF was reported in other effluent DOM (Saadi et al 2006;Hur et al 2008).…”
Section: Spectroscopic Characteristics For Freshly Produced Dommentioning
confidence: 67%
See 1 more Smart Citation
“…However, fluorescence patterns of treated sewage appear to depend on the effluent composition and the type of the treatment operations (Janhom et al 2009). The presence of relatively high PLF was reported in other effluent DOM (Saadi et al 2006;Hur et al 2008).…”
Section: Spectroscopic Characteristics For Freshly Produced Dommentioning
confidence: 67%
“…Both peaks were more pronounced for the effluent DOM and the terrestrial DOM. The former is known to be a predominant fluorescence portion of aquatic DOM in rivers and lakes (Baker 2001;Hur et al 2008). Here, four fluorescence regions were assigned to protein-like (PLF), fuvic-like (FLF), humic-like (HLF), terrestrial humic-like fluorescence (THLF), each of which corresponds to the integrated areas of the fluorescence intensities at the wavelength of 250-300, 300-380, 380-420, and 420-600 nm, respectively (Hur et al 2009b).…”
Section: Spectroscopic Characteristics For Freshly Produced Dommentioning
confidence: 99%
“…For instance, Ahmad and Reynolds (1999) have suggested this method for on-line process control in sewage treatment plants. Subsequently, other studies have implied the use of fluorescence spectroscopy as a potential monitoring tool for recycled water (Henderson et al,2009), drinking water treatment processes (Cheng et al, 2004;Bieroza et al, 2009), urban watersheds with sewage effluents (Hur et al, 2008) and evaluation of DOM composition and concentration in relation to the production of disinfection by products during drinking water chlorination (Spencer et al, 2007 and references therein). However, many issues have to be clarified before using this method for the previously mentioned application: possibility for automated data analysis, optimized calibration procedure to ensure reliability and repeatability of results and optimum instrument configuration (Henderson et al, 2009).…”
Section: Potential Applicationsmentioning
confidence: 99%
“…For example, the specific absorbance at 200 nm wavelength (UV 200 ), 254 nm (UV 254 ), and 280 nm (UV 280 ) have been analyzed with BOD, DOC, and total nitrogen (TN) concentration considering wastewater samples (Nataraja et al, 2006) and surface waters affected by sewage (Hur et al, 2008;Hur and Cho, 2012). The results of Nataraja et al (2006) indicated that UV 280 could be useful to estimate the BOD concentration, with good correlations for raw nonfiltrate effluent.…”
mentioning
confidence: 99%
“…Based upon the same principles, tryptophan-like fluorescence peak and humic-like fluorescence peak are often correlated with BOD, TOC, and DOC concentration (Baker, 2002;Cumberland and Baker, 2007;Hudson et al, 2007;Hur et al, 2008;Hur and Cho, 2012). In a study to evaluate the possibility of using fluorescence spectrometry as a substitute for BOD testing, Hudson et al (2007) found strong correlations for a wide variety of samples.…”
mentioning
confidence: 99%